Quadriceps femoris cross-sectional area and specific leg strength: relationship between different muscles and squat variations - Filip Kojic (PeerJ Inc., 2021)
Background The aim was to determine the relationship between the cross-sectional area of the quadriceps femoris and strength performance in the deep and parallel barbell squat. Methods The sample included 16 university students (seven female, 24.1 ± 1.7 years). Muscle strength was expressed as external load, including the one-repetition maximum and the body mass segments involved (calculated according to Dempster’s method). The cross-sectional area of the quadriceps femoris muscles was determined using ultrasound, while leg muscle mass was measured using the Bioelectrical Impedance method. Results The cross-sectional areas of the three vastii muscles and leg muscle mass showed moderate to strong correlation with external load in both squat types (r = 0.509–0.873). However, partial correlation (cross-sectional area of quadriceps femoris muscles were controlled) showed significant association only between leg muscle mass and deep squat (r = 0.64, p < 0.05). The cross-sectional area of the vastus lateralis showed a slightly higher correlation with external load in the parallel than in the deep squat (r = 0.67, p < 0.01 vs. r = 0.59, p < 0.05). The regression analysis extracted the vastus medialis cross-sectional area as the most important factor in manifesting strength (parallel squat: R2 = 0.569; deep squat: R2 = 0.499, both p < 0.01). The obtained results suggest that parallel squat strength depends mainly on the cross-sectional area of the vastii muscles, while it seems that the performance in the deep squat requires an additional engagement of the hip and back extensor muscle groups.